Domain knowledge model for embodied conversation agent - Goh, Ong Sing; Fung, Chun Che; Depickere, Arnold; Wong, Kok Wai; Wong, Wilson Yik Sen (CIRAS, 2005)
This paper presents and discusses several technical issues in implementing the conversation intelligent agent. In this work, we focus on domain knowledge models that enable structured queries on the field of epidemic crisis. We will simulate this system with sample conversation taken from our target Domain-Specific knowledge on the recent world epidemic crisis, Severe Acute Respiratory Syndrome (SARS). A solution would be to incorporate the conversation system embodied intelligent agent which will allow a more user-friendly interaction. The system does not only match a query against a database of keywords from our domain knowledge model but also help the user navigate through the document space until the appropriate information are found using the "URLs push" technique.